The Association Between Disease, Production and Culling in a University Dairy Herd - Cobo-Abreu, R. (1979)
The impact of ten diseases of dairy cattle on milk production, calving interval and culling were studied in a university operated dairy herd. Cows with clinical mastitis, ketosis or displaced abomasum had lowered milk production. Cows with metritis, retained placenta, cystic graafian follicles or ovarian hypofunction had longer calving intervals. Cows with clinical mastitis, metritis, pneumonia or retained placenta had increased risks of culling. The relationship between disease and culling was based on the medical history of culled and nonculled cows using a case control approach. Therefore, it is likely that in many cases, the association between disease and culling is due to the impact of that disease on productivity.